A flexible metallic TiC nanofiber/vertical graphene 1D/2D heterostructured as active electrocatalyst for advanced Li–S batteries. Issue 7 (9th June 2021) - Zhang, Yongshang; Zhang, Peng; Zhang, Shijie; Wang, Zheng; Li, Neng; Silva, S. Ravi P.; Shao, Guosheng
Abstract: The realistic application of lithium–sulfur (Li–S) batteries has been severely hindered by the sluggish conversion kinetics of polysulfides (LiPS) and inhomogeneous deposition of Li2 S at high sulfur loading and low electrolyte/sulfur ratio (E/S). Herein, a flexible Li–S battery architecture based on electrocatalyzed cathodes made of interfacial engineered TiC nanofibers and in situ grown vertical graphene are developed. Integrated 1D/2D heterostructured electrocatalysts are realized to enable highly improved Li + and electron transportation together with significantly enhanced affinity to LiPS, which effectively accelerate the conversion kinetics between sulfur species, and thus induce homogeneous deposition of Li2 S in the catalyzed cathodes. Consequently, highly active electro‐electrocatalysts‐based cells exhibit remarkable rate capability at 2C with a high specific capacity of 971 mAh g −1 . Even at ultra‐high sulfur loading and low E/S ratio, the battery still delivers a high areal capacity of 9.1 mAh cm −2, with a flexible pouch cell being demonstrated to power a LED array at different bending angles with a high capacity over 100 cycles. This work puts forward a novel pathway for the rational design of effective nanofiber electrocatalysts for cathodes of high‐performance Li–S batteries. Abstract : Novel method was developed for in situ growth of vertical graphene with simultaneous conversion of the substrate TiO2 nanofibers into TiC ones, with well‐interconnected interfaces within the metallic VG/TiC 1D/2D heterostructured electrocatalyst enabling fast redox kinetics essential for Li–S cells. This work offers a novel avenue for the fabrication of high‐performance cathode critical to practical high‐energy‐density Li–S batteries.